The Influence of Using Edmodo Media with the Discovery Learning Learning Model on Science Learning Outcomes on Pressure in Substances - Jumaeroh, Siti; Chetri, Deepak Raj; Govender, Hogantharanni (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: The purpose of this study was to determine the effect of Edmodo media with the discovery learning model on science learning outcomes on the material on pressure in substances. Methodology: This type of research is quasi-experimental quantitative. Sampling in this study was carried out by purposive sampling, namely class VIII D (experimental class) and class VIII E (control class) of junior high school, with 30 students and 28 students respectively. Data collection techniques use questions, questionnaires, observation sheets and documentation. This research instrument includes questions, questionnaires and observation sheets. Hypothesis testing is carried out using correlation coefficients and simple linear regression. Main Findings: There is an influence of 20.5% between two variables on the results of the simple linear regression test with a significance value of 0.015. So it can be concluded that there is an influence of Edmodo media with the Discovery Learning learning model on science learning outcomes regarding pressure in substances. Novelty/Originality of this study: The results of this study can be a basis for the development of Edmodo learning media or the further application of Edmodo media. In addition, it also becomes an added value to the scientific knowledge in the field of education in Indonesia.